2011
DOI: 10.1007/s10165-011-0577-6
|View full text |Cite
|
Sign up to set email alerts
|

Radiological features and therapeutic responses of pulmonary nontuberculous mycobacterial disease in rheumatoid arthritis patients receiving biological agents: a retrospective multicenter study in Japan

Abstract: ObjectiveThis study was performed to evaluate the radiological features of and therapeutic responses to pulmonary disease caused by nontuberculous mycobacteria (NTM) in the setting of biological therapy for rheumatoid arthritis (RA).MethodsWe conducted a retrospective chart review of 13 patients from multiple centers who had developed pulmonary NTM disease during biological therapy for RA, including infliximab, etanercept, adalimumab, and tocilizumab.ResultsMost cases were asymptomatic or resulted in only comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 31 publications
2
20
0
2
Order By: Relevance
“…Similar to the findings of previous studies, our results showed favourable clinical outcomes in patients with NTM disease [19,20]. In addition, the clinical outcomes of NTM patients did not differ significantly compared with those of TB patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to the findings of previous studies, our results showed favourable clinical outcomes in patients with NTM disease [19,20]. In addition, the clinical outcomes of NTM patients did not differ significantly compared with those of TB patients.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, as clinicians are concerned about the development of TB in patients treated with TNF-a inhibitors, there is a focus on screening and treating latent TB infection (LTBI) before administering TNF-a inhibitors. Although reports of NTM lung disease in patients treated with TNF-a antagonists have been published [5,12,19,20], clinical data on NTM lung disease developed during anti-TNF therapy is lacking. Our results indicate that development of NTM lung disease was during anti-TNF-a therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the onset of pulmonary NTM disease in RA patients appears to spread from pre-existing lung lesions, such as those involving bronchiectasis or nodules (12). However, it is currently unclear whether these preexisting abnormalities reflect the subclinical presence of pulmonary NTM colonization or constitute an extra-articular manifestation of RA.…”
Section: Discussionmentioning
confidence: 99%
“…These RA patients included two individuals who had been treated with TNF antagonists (11,12) and two who had not been treated with biological DMARDs (13,14). Two of these four cases were fatal (11,13).…”
Section: Discussionmentioning
confidence: 99%
“…No Japão, não houve aumento do número de casos de doença por micobactérias não tuberculosas. 205 Evidências recentes não demonstraram aumento da taxa de infecção da ferida operatória em pacientes com AR e em uso de TOCI após realização de artroplastia total de joelho ou quadril. 206 Recomenda-se suspensão do TOCI, pelo menos, quatro semanas antes do procedimento.…”
Section: Infecçõesunclassified